Investigation of acoustic properties of compressed wheat bran flakes - Ranachowski, Z.; Gondek, E.; Lewicki, P. P.; Marzec, A. (Archives of Acoustics, 2005)
The authors of this paper analysed Acoustic Emission (AE) signal generated during compression test of wheat bran flakes. Three AE descriptors were applied to process the results of the tests: counting of total number of EA events, average event duration and partition power spectrum slope. It was found that the presented descriptors correlate with the measured level of specimen structural moisture and one descriptor can be used in investigation of the effect of the loss of the perceived crispness in moistured product. The described methods of data processing can be applied to food product quality assessment procedures. Key words: food texture evaluation, crispness evaluation, acoustic emission.